Perspective of vibrational spectroscopy analytical methods in on‐field/official control of olives and virgin olive oil. Issue 1 (30th June 2016) - Nenadis, Nikolaos; Tsimidou, Maria Z.
Abstract : Vibrational spectroscopic techniques, infrared (near, mid, far) and Raman that are based on the continuous vibrational motion of the atoms in the corresponding bonds of the compounds correlate in a unique way the physical properties of materials in the gaseous, solid, or liquid state with the molecular structure. Olive industry and olive oil official control may benefit from the introduction of these powerful techniques to address quality and authenticity issues. This review focuses on evidence obtained from comparative studies among different vibrational techniques for the same set/s of samples or from the same instrumentation. It also assists the forum of discussion on what is needed for their standardization in order to find their place in the official control of the end product. The need for validation guidelines regarding the management of the instrument as well as the construction of the calibration model is highlighted. The latter depends heavily on the reference method employed. An extended list of references covering the characteristics of the techniques, advancements in instrumentation, general applications to oils and fats, and those useful for on‐field and official control of olive and olive oil is also given. Practical application : Vibrational spectroscopic techniques coupled to chemometrics can modernize olive and olive oil analysis from the field to the official control at the borders and in the market. As it occurs already for many decades in the field of other high added value commodities, i.e., milk, meat, wine, the value of the multiple type of information acquired with little sample manipulation should be recognized by all interested parties in the olive sector (stakeholders, authorities, researchers). Qualitative and quantitative information from field to the table (quality, adulteration, authentication). Abstract : Qualitative and quantitative information from field to the table (quality, adulteration, authentication).